4D Trajectory Design for Vision Only Sense and Avoid Flight Test *. Issue 1 (July 2017) - Melczer, Mark; Bauer, Peter; Bokor, Jozsef
Abstract: In order to test an aircraft's Sense & Avoid system featuring vision based detection and avoidance, a test track is needed to be constructed. The easiest way is to design two parallel paths which removes the need for timing. However, intersecting paths are needed to be constructed as well, which turns the design process into a 4D problem with critical timing. The paper introduces geometry generating methods in calm and in windy conditions, consequently validating them with the help of Software-In-The-Loop (SIL) Monte Carlo simulation and Hardware-In-The-Loop (HIL) simulations.